A modelling study on the frosting characteristics of a novel dual-fan outdoor coil in an Air Source Heat Pump unit. (5th March 2023) - Bai, Xiaoxia; Liu, Shengnan; Deng, Shiming; Zhang, Long; Wei, Minchen
Highlights: A dynamic model for an ASHP with dual-fan outdoor coil was developed and validated. Evener frosting was achieved by adjusting fan mode for higher heating performances. Similar alternate time interval of two fans led to smaller difference in frost thickness. The averaged output heating capacity and COP may be improved by 2%–12.7%. Abstract: Uneven frosting along the airflow direction in a traditional outdoor coil in air source heat pumps (ASHPs) was inevitable due to a fixed one-way outdoor airflow direction, causing a rapid deterioration in heating performances of ASHPs. To alleviate this uneven frosting phenomenon, a novel dual-fan outdoor coil where air flow direction can be alternately reversed was proposed in a previous experimental study. To more effectively and comprehensively study the operating characteristics of ASHPs having the dual-fan outdoor coil at different fan operating modes, with different configurations and under different operating ambient conditions, a dynamic mathematical model for the experimental ASHP having the dual-fan outdoor coil was developed and experimentally validated. Then a follow-up modelling study for different operating modes of the two fans, fin pitches and operating ambient conditions was carried out using the validated model. The modelling results demonstrated that by optimizing fan operating mode, the difference in frost thickness between the windward and leeward sides of the dual-fan outdoor coil can be reduced by up to 77.3 %, the averaged output heating capacity and COP improved by up to 11.1 % and 12.7 %, respectively, and the number of switching operation of the two fans decreased by 55.6 %. Besides, the recommendations for using the dual-fan outdoor coil at different operating modes of the two fans, different fin pitches and operating ambient conditions were also made. The model can be used as a useful tool in helping achieve higher operating efficiency for ASHPs having the novel dual-fan outdoor coil.